1981
DOI: 10.2527/jas1981.5351333x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hormone Response and Fertility in Dairy Heifers Treated with Norgestomet and Estradiol Valerate2

Abstract: Seventy postpuberal dairy heifers were assigned to remain untreated (n = 26) or to receive the Syncro-Mate-B (SMB) treatment (n = 44). Untreated heifers were inseminated at 12 hr after detection of estrus, while SMB-treated heifers were inseminated either at 48 hr after implant removal (group 1) or at 12 hr after detection of estrus (group 2). Jugular blood was collected at regular intervals from four untreated heifers and from 20 SMB heifers. In untreated heifers, estradiol-17 beta (E) was unchanged throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
1
2
0
1
Order By: Relevance
“…One of these three conceived to the artificial insemination. This variability was similar to that observed by Kazmer et al (1981) in dairy heifers synchronized with norgestomet and estradiol. Based on the low frequency of asynchronism observed in our study, we conclude that timing of the LH surge relative to estrus is not a major contributor to the low fertility reported for 48-h timed insemination.…”
Section: Results and Discussion 20supporting
confidence: 87%
See 2 more Smart Citations
“…One of these three conceived to the artificial insemination. This variability was similar to that observed by Kazmer et al (1981) in dairy heifers synchronized with norgestomet and estradiol. Based on the low frequency of asynchronism observed in our study, we conclude that timing of the LH surge relative to estrus is not a major contributor to the low fertility reported for 48-h timed insemination.…”
Section: Results and Discussion 20supporting
confidence: 87%
“…The group consisted of two heifers that exhibited estrus later than 54 h after implant removal, five that were not observed in estrus, and three that had an LH surge later than 12 h after estrus. Zaied et al (1976), Spitzer et al (1978) and Kazmer et al (1981) found conception rates similar to those of the optimal timing group in cattle without Brahman breeding. It is apparent that heifers that displayed estrus later than 54 bEstrus < 54 h after implant removal and LH surge within 12 h after onset of estrus.…”
Section: Results and Discussion 20mentioning
confidence: 81%
See 1 more Smart Citation
“…Como o horário da inseminação em relação à ovulação é um fator importante na taxa de concepção, trabalhos têm sido feitos com o objetivo de diminuir a variação no tempo de ovulação em animais sincronizados, visando melhor fertilidade (Kazmer et al, 1981) Apesar das suas vantagens, o número de fazendas que empregam o uso da inseminação artificial como rotina ainda é pequeno. No…”
Section: Inseminação Artificial Em Tempo Fixounclassified